Respuesta :

Answer:

1: [tex]3[/tex]×[tex]2[/tex]

2: [tex]y^6[/tex]

Step-by-step explanation:

1:

Multiply the numbers: [tex]y(^3^*^2)[/tex]

[tex]3*2 = 6[/tex]

Write it without exponents:

[tex]y * y * y * y *y *y[/tex] so [tex]6y[/tex].

2:

[tex](y^3)^2[/tex]

Apply exponent rule : [tex](a^b)^c=a^b^c,[/tex] assuming [tex]a\geq 0[/tex]

[tex](y^3)^2=y^3^*^2[/tex]

[tex]=y^3^*^2[/tex]

Multiply the numbers: [tex]3 * 2 = 6[/tex]

[tex]= y^6[/tex]

Hope I helped! If so, may I get Brainliest and a Thanks?

Thank you, have a good one! =)